Guidelines for safe and optimum neck dissection: a review article - Murchite, Sheetal A.; Gowtham, Thakut; Kadiyal, Abhinandan Milind; Gaikwad, Vaishali Vinayak; Tiwari, Ashutosh (International Surgery Journal, 2021)
Head and neck cancer is the sixth most common cancer worldwide. The single most important factor affecting prognosis for squamous cell carcinoma is the status of the cervical lymph nodes. Metastasis to the regional lymph nodes reduces the 5-year survival rate by 50% compared with that of patients with early-stage disease. The American cancer society reports that 40% of patients with squamous carcinoma of the oral cavity and pharynx present with regional metastases to the cervical lymph nodes. This activity presents the steps for safe and optimum neck dissection. Objectives of the study were to identify the anatomical structures in neck dissection, review the complications of head and neck surgery and summarize the importance of care coordination and to improve outcomes for patients undergoing head and neck surgery.